Application of Behavioural Health Models in Elderly Health Promotion: A Scoping Review - Ms. Torsha Biswas; Prof. Dr. Suil Kumar Dular; Prof. Deepa Mukherjee (The Bioscan, 2025)
As the global population continues to age, the health needs of older adults have become a major focus of public health. Aging is associated with increased risks of chronic diseases, functional decline, and mental health challenges, making health promotion for older adults a critical priority. However, the complex physical, cognitive, and social changes that accompany aging require tailored strategies to support healthy behaviors and lifestyles. Traditional health promotion methods may fall short if they do not consider the unique circumstances of elderly individuals.